Regression of mature lymphatic vessels in the cornea by photodynamic therapy. Issue 3 (10th January 2014) - Bucher, F; Bi, Y; Gehlsen, U; Hos, D; Cursiefen, C; Bock, F
Abstract : Background: Corneal (lymph) angiogenesis is a predominant risk-factor for immune rejection after transplantation. Techniques to regress pre-existing pathological corneal lymphatic vessels prior to transplantation are missing so far. Therefore we analysed the possibility to regress corneal lymphatic vessels by photodynamic therapy (PDT), after intrastromal verteporfin injection. Methods: Combined hemangiogenesis and lymphangiogenesis was induced in female BALB/c mice using the murine model of suture-induced inflammatory neovascularisation. Thereafter, the treatment group received an intrastromal injection of verteporfin (controls: phosphate buffered saline (PBS)) followed by PDT. Corneas were excised at different time points (1 day, 5 days and 10 days) after PDT and corneal whole mounts were stained with CD31 and LYVE-1 to quantify hemangiogenesis and lymphangiogenesis. Results: Whereas blood vessels showed no significant reduction after PDT, lymphatic vessels could significantly be reduced with PDT after intrastromal verteporfin injection: 1 day after PDT, lymphatic vessels were reduced by 62% (p=0.20). After 5 days and 10 days, lymphatic vessels were reduced by 51% and 48% (p<0.001), respectively. Conclusions: This study for the first time shows that PDT after corneal intrastromal verteporfin injection can selectively regress lymphatic vessels. This may become a new 'preconditioning strategy' to reduce pre-existing corneal lymphatic vessels prior to transplantation and thereby reduce allograft rejection in high-risk patients.